Housing in Canadian Cities: An Agenda and Review of Sources - Harris, Richard (Urban History Review / Revue d'histoire urbaine, 1986)
Historical scholars have not recognized the importance of housing in modern Canada. There is no overall conception of what needs to be known on the subject. In terms of the consumption as opposed to the production of housing, residential segregation, tenure, housing costs and conditions are the four major aspects to be considered. Their full significance can be understood only when viewed as part of the experience of social groups, particularly those defined in terms of class, ethnicity and gender. In describing social variations in housing consumption the most generally useful sources are the Census, City Directories and Assessments. The Censuses for 1871, 1941 and especially 1931 are rich but neglected sources of information on housing, while City Directories are more reliable than many think. These sources could illuminate changes in housing consumption in the first half of the twentieth century, a period of marked scholarly neglect.